Addressing basic need insecurities during the COVID-19 pandemic: a multi-case study of administrators at three community colleges in Texas - Prochaska, Dayna Lynn (Kansas State University, 2023)
Basic Need Insecurities often impact the ability of community college students to persist and complete their goals. The COVID-19 pandemic exacerbated BNI for students’ forcing administrators to respond to and address BNI. This study will highlight administrators’ responses toward BNI and focus on the changes and/or services administrators implemented to support students and address BNI during the COVID-19 pandemic. The purpose of this study was to gain a deeper understanding of the leadership strategies and competencies that contributed to how administrators responded to BNI during the COVID-19 pandemic and to identify the changes and/or services that were implemented to support students during this time. The findings from this study could provide value to leadership preparation programs and provide insight into community colleges addressing BNI. Due to the context of this research, the chosen methodology for this study was a qualitative multi-case study design comprised of interviews with administrators from three community college campuses in Texas in addition to document reviews. Additionally, interviews were semi-structured to allow the researcher to use structured questions to guide the interview and provide an opportunity to use probes and spontaneous questions to explore and gain a deeper understanding of the topic (Wilson, 2014). This study explored competencies administrators in Texas used to address BNI during the COVID-19 pandemic and identified changes and services implemented to support students’ BNI. Demonstrating compassion and care was reported to be critical to supporting students during the pandemic. Creating open communication that was clear, concise, and constant and encouraging collaboration was vital to successfully leading and supporting students BNI. Empowering employees with the knowledge and tools to support students during the pandemic was also an essential competency to successfully leading and supporting students BNI during the pandemic. Many changes and services were implemented during the pandemic to support students' BNI; most revolved around adding BNI services, including food pantries and emergency aid. The most impactful implementation, however, was the addition of a one-stop shop where wrap-around services are provided to address BNI, including mental health, food pantries, clothes closets, personal hygiene products, childcare, transportation, emergency aid, and housing assistance.
Keywords: Basic need insecurity; COVID-19; Pandemic; Competencies; Support services